Toxoplasmosis. Estudio clínico patológico de los dos primeros casos reportados en Costa Rica - Céspedes, Rodolfo (1955)
The first two cases of toxoplasmosis recognized in Costa Rica are presented. Both occurred in children, of 18 mos. and 6 years of age respectively, from the rural zone of the Pacific slope in Costa Rica. The etiologic diagnosis was not made at the clinic in either case; it was a surprise finding during the routine histopathologic study of the first case, and was suspected during the macroscopic autopsy in the second case, in which isolated forms and pseudocysts or nests of Toxoplasma were quickly found in myocardium smears stained with Giemsa. It was also possible to isolate Toxoplasma gondii from mice six days after inoculation with myocardium and spleen from the second case. Some fundamental facts are stressed of the clinic cases: The process began as an indeterminate infective state which apparently eured, followed later by a generalized edematous syndrome which led the clinicians to suspect the presence of an acute glomerulonephritis. Urine was normal in both cases. It is difficult to attribute some of the symptoms of the first case to toxoplasmosis since the process evolved simultaneously with a picture of jungle yellow fever. In the second case there is the clear antecedent of a generalized skin emption preceding the edematous syndrome. Later a picture of global cardiac insufficiency set in, with fatal outcome in ten days. The patient was also suffering a severe aneylostomatic anemia of 1.500.000 erythrocytes. Thus neither case was a pure toxoplasmosis. The edematous syndrome of the first case may be explained as due to hypoproteinemia of 3.4 gm. per cent. No blood protein tests were made in the second case, but it is assumed to be low since there was a severe aneylostomatic anemia. Edema here was part of the cardiac insufficiency picture. Four organs showed important lesions referrable to toxoplasmosis: 1) The heart, which showed myocardial flaccidity, acute exudative myocarditis with interstitial edema, fragmentation of fibres, decrease or loss of trans verse striation, presence of nests or pseudocysts with toxoplasms within the fibres, cellular infiltration with mono nuclear prevalence, some eosinophiles, and proliferation ft fibroblasts. 2) 111e brain, showing edema, toxoplasma nests in the thalamus and in the annular protuberance, and moderate inflammatory cellular infiltration, at times perivascular. 3) The lungs, with macroscopic bronchopneumonial foci in which histological examination showed accentuated exfoliative alveolitis and moderate leucocyte infiltration. No parasites were found in the lungs. 4) The spleen, showing reticulo-histiocytary hyperplasia, and some macro phages containing toxoplasms. No lesions were found in the eyeball. From the epidemiologic viewpoint, the facts are stressed that: 1) both patients originated in the same geographic region, o f warm humid climate. 2) environmental hygienic and nutritional conditions are deficient in that region. 3) other diseases were coincídent wíth toxoplasmosis, yellow fever in one case, serious ancylostomasis, trichocephalosis and ascaridiosis in the other. 4) there was a high infant mortality in the family of case one: 5 dead before 18 months of age out of 8 born. 5) the manner of entry of the parasite into the human organism could not be determined from the anatomo-clinic and epidemiologic study of these two cases.